2010
DOI: 10.1002/arch.20384
|View full text |Cite
|
Sign up to set email alerts
|

cDNA cloning and induction of tyrosine hydroxylase gene from the diamondback moth, Plutella xylostella

Abstract: We cloned a full-length tyrosine hydroxylase cDNA from the integument of the diamondback moth, Plutella xylostella. In the phylogenetic tree, tyrosine hydroxylase (PxTH) clustered with the other lepidopteran THs. Serine residues in the PxTH sequence, namely Ser(24), Ser(31), Ser(35), Ser(53), and Ser(65), were predicted to be the target sites for phosphorylation based on PROSITE analysis. In particular, Ser(35) of PxTH is highly conserved across a broad phylogenetic range of animal taxa including rat and human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
(54 reference statements)
0
1
0
Order By: Relevance
“…The general finding is that expression of tyrosine hydroxylase and dopa decarboxylase is significantly induced following infection [12], [53], while we found that tyrosine hydroxylase was up-regulated and dopa decarboxylase was down-regulated (Table 3). …”
Section: Resultsmentioning
confidence: 58%
“…The general finding is that expression of tyrosine hydroxylase and dopa decarboxylase is significantly induced following infection [12], [53], while we found that tyrosine hydroxylase was up-regulated and dopa decarboxylase was down-regulated (Table 3). …”
Section: Resultsmentioning
confidence: 58%